State And Religion Relations in The Republic of Uzbekistan - Murodov Shuhrat Komil ugli (Peerian Journals Publishing, 2024)
In the Constitution of the Republic of Uzbekistan, "Religious organizations and associations are separated from the state and work is carried out on the basis of the principle of equality before the law. In our study, it is permissible to admit that the scope of the reforms implemented in the religious sphere as a democratic country is extremely high
Keywords: State; religion; Quran; confession